Analisis Penanganan Pembelajaran Dan Sosialisasi Siswa Autis Di Tempat Bimbingan Belajar Anak Berkebutuhan Khusus Widya Wicara Serang - Nurhayati Kusuma Dewi; Yahdinil Firda Nadirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the learning and socialization of autistic students at the Widya Wicara Serang Special Needs Tutoring Center for Children with Special Needs. The study used a descriptive qualitative method, using interviews and observations with teachers and autistic students. The results showed that autistic students experience difficulties in verbal and nonverbal communication, social interaction, attention span, and repetitive behaviors, which impact the learning process. Teachers implemented various approaches, such as the use of visual aids, concrete media, individual approaches, and consistent reinforcement strategies. Observations showed positive developments, including reduced tantrums, improved ability to follow simple instructions, and increased responsiveness to environmental stimuli. Interviews with teachers revealed that collaboration between teachers and parents plays a crucial role in supporting the effectiveness of interventions, particularly regarding the daily routines and eating patterns of autistic children. The greatest challenge in learning is limited communication and social interaction, requiring teachers to provide repeated sensory stimulation and easy-to-understand, step-by-step communication. This study emphasizes the importance of using structured methods, visual media, and intensive collaboration between teachers and parents to support the academic, behavioral, and social development of autistic students.